The idea of the exclusion of necrophilic attitudes in critical psychology of Erich Fromm - Śliwerski, Bogusław (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
The subject of the analysis is the category of the inclusion as a process that does not only apply to people with special developmental or life needs, but also to social sciences, which as a result of the positivist research paradigm have divided and separated from each other. Meanwhile, human upbringing requires the inclusion of biophilic orientation towards life in all social sciences, whose achievements should be considered and applied to improve educational processes. The Author borrows inspiration from the typology of human attitudes of Eric Fromm, because it makes readers aware of the negative effects of necrophilia in interpersonal relationships. The Author analyses Fromm’s approach against the background of selected ideas of Polish pedagogical views.